Numerical Validation of Flexitank Hydrodynamic Performance under Different Driving Conditions - Azahar, Mohamad Amirur Rahman; Darlis, Nofrizalidris; Izuan Amin Ishak; Syafiqah Ruqaiyah Saiful Azam; Syabillah Sulaiman; Muhammad Adli Mustapa (International Journal of Integrated Engineering, 2025)
Flexitanks have revolutionized bulk liquid logistics through their cost-effectiveness and adaptability, yet their inherent flexibility introduces complex hydrodynamic challenges, particularly due to liquid sloshing during dynamic vehicle motion. This study presents a numerical validation of flexitank hydrodynamic performance under realistic driving conditions, focusing on the pressure response and fluid motion within the flexible containment. A 1:8 scaled flexitank prototype was experimentally tested to measure transient wall pressures and deformation using force-sensitive resistor (FSR) sensors, while a computational fluid dynamics (CFD) model was developed in Ansys Fluent to simulate the internal flow behavior. Comparison between experimental and numerical results demonstrated strong correlation, achieving a percentage different error below 8.5% throughout the driving cycle. The analysis further revealed that deceleration events generated 14–18% higher wall pressures than acceleration phases due to inertial and pressure wave effects. The validated CFD framework provides a reliable predictive tool for understanding sloshing-induced behavior in flexible liquid containment systems and contributes to safer, more efficient bulk liquid transport design.